PENINGKATAN NILAI GIZI MIKRO KUDAPAN LOKAL MELALUI SUBTITUSI TEPUNG IKAN GABUS UNTUK PENCEGAHAN STUNTING DI SULAWESI SELATAN - Nadimin Nadimin; Retno Sri Lestari (Media Kesehatan Politeknik Kesehatan Makassar, 2019)
ABSTRACT Local snacks are used to being consumed by local people, including children under five, but the local cultural products have unbalanced nutritional content, which generally only contains energy sources. On the other hand, in this area also has fish food ingredients such as "cork fish" which are rich in protein and vitamins and minerals. The addition of cork fish flour can produce local food products that contain complete and balanced nutrients for supplementary food for toddlers. This research was carried out to develop local services as a model for improving nutritional status in children under five. The design of the study uses Static group comparison design, which compares the levels of local nutritional nutrients from several concentrations of cork fish meal 0% and 5%. Nutrient content of cork protein fish meal 73.81%, iron 0.9%, zinc 0.42%, calcium 35.38%. Local TIG snacks (cork fish meal) contain 353 mg calcium, pospor 546 mg, iron 9 mg and zinc 4.4 mg every serving. Addition of TIG above 5% can meet micronutrient needs in children under five. Keywords: nutritional value, local snacks, cork fish meal